CdSe Quantum Dots Induce Cellular Differentiation in HL-60 Cells - Saran, Amit D.; Bellare, Jayesh R. (Nanoscience & Nanotechnology-Asia, 2020)
Background: CdSe QDs, synthesized using a green micro-emulsion method, have been evaluated for their potential in inducing HL-60 differentiation by employing various biochemical assays and as cellular imaging agents. Methods: CdSe QDs have been found to effectively induce differentiation with lower rate of cell apoptosis as compared with the positive control (DMSO). Results: Our results exhibit effective induction of HL-60 differentiation by CdSe QDs implicating their therapeutic role in cancerous cells in addition to their usual application as cell-imaging agents. Conclusion: Our studies report that the chemo-preventive properties of CdSe exhibit great potential and further tailored-synthesis and cell-differen-tiations studies have a promising future in the preventive treatment of HL60 cancerous tissue.
Keywords: microemulsion